Preliminary observations of tool-processing behaviour in Hawaiian crows Corvus hawaiiensis - Klump, Barbara C. (Commun Integr Biol, 2018)
Very few animal species habitually make and use foraging tools. We recently discovered that the Hawaiian crow is a highly skilled, natural tool user. Most captive adults in our experiment spontaneously used sticks to access out-of-reach food from a range of extraction tasks, exhibiting a surprising degree of dexterity. Moreover, many birds modified tools before or during deployment, and some even manufactured tools from raw materials. In this invited addendum article, we describe and discuss these observations in more detail. Our preliminary data, and comparisons with the better-studied New Caledonian crow, suggest that the Hawaiian crow has extensive tool-modification and manufacture abilities. To chart the full extent of the species’ natural tool-making repertoire, we have started conducting dedicated experiments where subjects are given access to suitable raw materials for tool manufacture, but not ready-to-use tools.